Mean Platelet Volume in Neonatal Sepsis: Meta-Analysis of Observational Studies - Toro-Huamanchumo, Carlos J. (2022)
“first_pagesettingsOrder Article Reprints Open AccessSystematic Review Mean Platelet Volume in Neonatal Sepsis: Meta-Analysis of Observational Studies by Carlos J. Toro-Huamanchumo 1ORCID,Cielo Cabanillas-Ramirez 2,3ORCID,Carlos Quispe-Vicuña 3,4ORCID,Jose A. Caballero-Alvarado 5ORCID,Darwin A. León-Figueroa 3,6ORCID,Nicolás Cruces-Tirado 7 andJoshuan J. Barboza 3,8,*ORCID 1 Escuela de Medicina, Universidad Cesar Vallejo, Trujillo 13007, Peru 2 Escuela de Medicina, Universidad Peruana de Ciencias Aplicadas, Lima 15023, Peru 3 Unidad de Revisiones Sistemáticas y Meta-Análisis, Tau-Relaped Group, Trujillo 13007, Peru 4 Sociedad Científica San Fernando, Universidad Nacional Mayor de San Marcos, Lima 15081, Peru 5 Facultad de Medicina, Universidad Privada Antenor Orrego, Trujillo 13007, Peru 6 Facultad de Medicina Humana, Universidad de San Martín de Porres, Chiclayo 14000, Peru 7 Facultad de Ciencias de la Salud, Universidad Señor de Sipán, Chiclayo 14006, Peru 8 Vicerrectorado de Investigación, Universidad Norbert Wiener, Lima 15046, Peru * Author to whom correspondence should be addressed. Children 2022, 9(12), 1821; https://doi.org/10.3390/children9121821 Received: 5 October 2022 / Revised: 21 November 2022 / Accepted: 22 November 2022 / Published: 25 November 2022 (This article belongs to the Section Pediatric Infectious Diseases) Download Browse Figures Review Reports Versions Notes Abstract Introduction: Early onset neonatal sepsis (EONS), particularly in preterm sepsis, is a potentially fatal issue. Evaluation of mean platelet volume (MPV) as an EONS predictor was the goal. Methods: Four databases were used to conduct a systematic evaluation of cohort and case–control studies. Up till the end of October 2022, 137 articles were found utilizing the search method. Following the review, 12 studies were included. Leukocytes, MPV, platelets, gender, birth weight, gestational age, mortality, and C-reactive protein (CRP) were all taken into account while analyzing the prediction of EONS. Inverse-variance methodology and the random-effects model were used. Using GRADE, the evidence’s quality was evaluated. Results: Neonatal patients with sepsis had significantly higher MPV levels than do neonates without sepsis (MD 1.26; 95% CI 0.89–1.63; p < 0.001). An increased MPV during the first 24 h postpartum was associated with high CRP values and high risk of neonatal mortality. In the investigations, the MPV cutoff for sepsis patients was 9.95 (SD 0.843). Overall certainty of the evidence was very low. Conclusions: The increased MPV during the first 24 h postpartum may be predictive of EONS and mortality. Future studies are warranted.“